Breakdown of Communication Between ATC and Pilot as a Cause of Aircraft Incident: A Literature Review - Riani Riani; Rany Adiliawijaya Putriekapuja; Elfi Amir (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Aviation Safety is highly dependent on effective communication between Air Traffic Controllers (ATCs) and pilots. Communication is a vital component of the Air Traffic Services (ATS) system, serving to prevent collisions, regulate air traffic flow, and provide essential safety information. However, data from the International Civil Aviation Organization (ICAO) and Indonesia's National Transportation Safety Committee (KNKT) indicate that approximately 60–70% of aviation incidents are caused by human error, with Communication Breakdown being one of the most significant contributing factors. In Indonesia, the rapid increase in air traffic following the COVID-19 pandemic has heightened the risk of miscommunication, particularly during peak traffic periods and emergency situations. This study aims to comprehensively analyze the factors contributing to Communication Breakdown, its impact on Aviation Safety, and evidence-based mitigation strategies identified in the literature. The study employed a literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. A total of 10 nationally accredited SINTA 3–6 journals published between 2018 and 2025, along with KNKT reports and ICAO documents, were analyzed thematically. The findings identified four dominant factors contributing to Communication Breakdown: the use of non-standard Phraseology, English language proficiency below ICAO Level 4, ATC workload and fatigue, and technical factors such as frequency interference and stuck microphone. The consequences of miscommunication include loss of separation, runway incursion, near miss incidents, and the potential for fatal accidents. Recommended mitigation strategies include strengthening ICAO English Proficiency training, implementing Controller–Pilot Data Link Communications (CPDLC)/Data Link technology, enforcing readback-hearback procedures, adopting Crew Resource Management (CRM) and Threat and Error Management (TEM), and improving fatigue risk management for ATCs. This study is expected to serve as a reference for AirNav Indonesia and aviation education institutions in enhancing communication standards to support Aviation Safety in Indonesia.